2017
DOI: 10.1111/maec.12462
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal variation in biomass of the deep‐sea red crab Chaceon affinis in Gran Canaria Island (Canary Islands, Eastern‐Central Atlantic)

Abstract: The spatial and temporal biomass distribution of Chaceon affinis and its vulnerability to fishing activity in Gran Canaria (Canary Islands) were investigated. The first goal was to assess the influence of the slope steepness and substrate on the size of crab patches, size of the crabs, and crab biomass. The second goal was to evaluate spatial and temporal variation in the biomass over a 15‐month period. The last goal was to assess the influence of fishing activity upon the reduction in the biomass over the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
1
0
0
Order By: Relevance
“…The distribution found in this study agrees with the general spatial structure observed for the species in other areas of the Azores (Pinho, Gonçalves, et al, ; Pinho, Martins, et al, ), Madeira and Canaries (González et al, ; López Abellán et al, ; Biscoito et al, , Triay‐Portella et al, ) or MAR (Zaferman & Sennikov, ), with highest abundance within the 700‐ to 900‐m strata and high variability among stations. However, abundances from the Voador and Gigante seamounts were significantly greater than those found in coastal areas of the Azores and at the same level of the abundance found on another hydrothermal vent (Pinho, Gonçalves, et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…The distribution found in this study agrees with the general spatial structure observed for the species in other areas of the Azores (Pinho, Gonçalves, et al, ; Pinho, Martins, et al, ), Madeira and Canaries (González et al, ; López Abellán et al, ; Biscoito et al, , Triay‐Portella et al, ) or MAR (Zaferman & Sennikov, ), with highest abundance within the 700‐ to 900‐m strata and high variability among stations. However, abundances from the Voador and Gigante seamounts were significantly greater than those found in coastal areas of the Azores and at the same level of the abundance found on another hydrothermal vent (Pinho, Gonçalves, et al, ).…”
Section: Discussionsupporting
confidence: 89%